2012
DOI: 10.1002/gepi.21699
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Rare Variant Effects Using Extreme Phenotype Sampling in Sequencing Association Studies

Abstract: In the increasing number of sequencing studies aimed at identifying rare variants associated with complex traits, the power of the test can be improved by guided sampling procedures. We confirm both analytically and numerically that sampling individuals with extreme phenotypes can enrich the presence of causal rare variants and can therefore lead to an increase in power compared to random sampling. While application of traditional rare variant association tests to these extreme phenotype samples requires dicho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
128
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 39 publications
2
128
0
Order By: Relevance
“…This selection strategy is not only boosting the typical power gains from selection but also concentrating the functional variants in the sample. As previously reported, 16 this is the critical step to the design of a rare variant association study. If individuals are not selected for the functional variants, there will be no power to detect the association.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This selection strategy is not only boosting the typical power gains from selection but also concentrating the functional variants in the sample. As previously reported, 16 this is the critical step to the design of a rare variant association study. If individuals are not selected for the functional variants, there will be no power to detect the association.…”
Section: Discussionmentioning
confidence: 89%
“…14 More recently, it has been established that extreme sampling performs better than random population-based sampling for single rare variants, with the apparent effect size increasing with more and more stringent selection thresholds, 15 but limited studies have explored the effect when variants are aggregated within a gene. Studies have shown that extreme sampling can enrich for the presence of causal variants 16,17 and, furthermore, that extreme phenotypic sampling and/or a twostage analysis can lead to gains in power. [17][18][19] Lee et al 20 compare available gene-based tests and discuss design strategies for RVASs.…”
Section: Introductionmentioning
confidence: 99%
“…This observation suggests that higher power may be achieved to contrast case-case dis/similarity against control-control dis/similarity instead of contrasting within-group comparisons against between-group comparisons. The suggestion echoes the implications in several recent work that the contrast of two extreme phenotype groups may improve the statistical power of rare-variant association tests (Guey et al 2011;Li et al 2011;Barnett et al 2013;Lee et al 2014).…”
Section: Introductionmentioning
confidence: 78%
“…In extreme phenotype sampling, individuals from the extremes of the trait distribution [39][40][41], individuals with large residuals after adjustment for nongenetic covariates [42] [39,42], particularly for small MAF. Analysis of selected samples is more complex, as specialized methods are required to adjust for the effects of ascertainment.…”
Section: Study Design and Rare Variantsmentioning
confidence: 99%
“…Analysis of selected samples is more complex, as specialized methods are required to adjust for the effects of ascertainment. Both burden-type tests and variance-based SKAT-type tests have been extended to account for extreme sampling [39,40]. Analysis of a secondary phenotype that is correlated with the phenotype defining the sampling scheme also requires a specialized regression model [44].…”
Section: Study Design and Rare Variantsmentioning
confidence: 99%